Congenital Mesoblastic Nephroma Presenting with Hematuria in a Neonate - Yao, Zhigang; Wang, Haili; Liu, Qingwei (Journal of Nippon Medical School, 2018)
Congenital mesoblastic nephroma (CMN) is a rare tumor of infancy. CMNs can be histologically divided into classic, cellular, and mixed subtypes. Cellular CMNs are difficult to differentiate from Wilms tumors. Herein, a neonate with cellular CMN accompanied by macroscopic hematuria, is described. The clinical, pathological, and imaging features of the disease are discussed.